Faktor-Faktor yang Berhubungan dengan Perilaku Penjamah Makanan Jajanan di Pantai Gandoriah Pariaman - Wusqa, Asy Syifa Urwatul; Nur, Erdi; Lindawati, Lindawati; Gusti, Awalia; Wijayantono, Wijayantono (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2025)
Food handlers are individuals who directly interact with food and its utensils, from preparation to serving. Observations at Gandoriah Beach, Pariaman, revealed unhygienic behaviors among food handlers, such as not wearing aprons, not washing hands with soap, and having long, dirty nails. This study aimed to identify factors associated with the behavior of street food handlers at Gandoriah Beach in 2022. An analytic survey method with a cross-sectional design was used. A sample of 45 food handlers was selected from a population of 68. Data were analyzed using the chi-square test with a 95% confidence level (α=0.05). The results showed that 66.7% of respondents had a high level of knowledge, 62.2% had a positive attitude, 56.6% worked in areas with poor sanitation facilities, and 53.3% demonstrated good behavior. There was a significant relationship between attitude and behavior (p=0.005), and between sanitation facilities and behavior (p=0.042), but no significant relationship between knowledge and behavior (p=0.113). It is recommended that food handlers improve sanitation facilities and consistently apply food hygiene and sanitation principles.